Societies and Cities in the Age of Instant Access - Miller, Harvey J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
We are on the verge of what many are calling the "second information revolution," based on ubiquitous access to both computing and information. Handheld communication devices will become portable and even wearable remote control devices for both the social and physical worlds. At the same time, access to information will likely flourish, with an explosion in the volumes of data collected and distributed by these new devices-volumes of information about people delivered to more and more people, in new ways. The technologies of instant access have potential to transform dramatically our lives, cities, societies and economies much like the railroad, telephone, automobile and Internet changed our world in the previous ages. This book contains chapters by leading international experts who discuss issues surrounding the impact of instant access on cities, daily lives, transportation, privacy, social and economic networks, community and education.
Societies and cities in the age of instant access -- Cities and the Built Environment -- The new middle landscape -- Imagining the recursive city: explorations in urban simulacra -- Download my building: How building information modeling will transform our cities -- Misses, near-misses and surprises in forecasting the informational city -- Activities in Space and Time -- Does instant access promote sedentary behavior? Putting physical activity on the instant-access-in-cities agenda -- Revisiting Hägerstrand's time-geographic framework for individual activities in the age of instant access -- Dynamic prisms and ''instant access'': linking opportunities in space to decision making in time -- Where do you want to go today [in attribute space]? -- Transportation -- Reexamining ICT impact on travel using the 2001 NHTS data for baltimore metropolitan area -- Influence of mobility information services on travel behavior -- Shared ride trip planning with geosensor networks -- Mobile Information Services -- Mobile ICT in public spaces and its impact on privacy -- The dimensions of locational privacy -- Location-based services: Enabling technologies and a concierge service model -- From cyberspace to DigiPlace: Visibility in an age of information and mobility -- Paradoxical consequences of location-based services (LBS): A tetradic analysis using McLuhan's laws of media -- Social and Economic Networks -- The evolving social geography of blogs -- Cell phones and places: The use of mobile technologies in Brazil -- Inter-firm relations in the age of instant access: Case of the U.S. logistics industry -- Community -- Rethinking public participation as instant access to virtual meetings -- Digital middletown: a glimpse at the information society.
Keywords: GEOGRAPHY; INFORMATION SYSTEMS; ARCHITECTURE; HUMAN GEOGRAPHY; GEOGRAPHY; GEOGRAPHY (GENERAL).; INFORMATION SYSTEMS APPLICATIONS (INCL.INTERNET).; HUMAN GEOGRAPHY; URBANISM